Characterisation of endophytic bacteria from Nam-Nam plants (Cynometra cauliflora) for antibacterial activity and production of plant growth promoting factors - Rabiatul Adawiyah Khalil,; Sharifah Aminah Syed Mohamad,; Nur Rahimatul Hayati Abdul Rahman,; Nurul Aida Kamal Ikhsan,; Norfatimah Mohamed Yunus,; Ajibola, Olaide Olawunmi; Nurliana Abd Mutalib,; Mohd Cairul Iqbal Mohd Amin, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Plant-beneficial microorganisms also known as endophytes colonize the inside healthy tissues of living plants and form mutualistic relationships with them. Endophytes are important components of the plant microbiome and give a variety of benefits to their hosts. Nam-Nam plant (Cynometra cauliflora), is an indigenous tree to Peninsular Malaysia with various medicinal properties. This study aimed to isolate and characterize endophytic bacteria from different parts of Nam-Nam plants such as leaves, stems, and roots. The ethyl acetate extracts from the endophytic bacteria were tested for their antibacterial activity against 7 bacterial pathogens. Plant growth promotion traits including starch hydrolysis, phosphate solubilization, nitrogen fixation, and indole-3 acetic acid (IAA) production were screened among the endophytic bacteria isolates. Molecular identification by 16S rRNA gene sequencing was performed for isolates with good antibacterial activity and plant growth promotion traits. A total of 33 endophytic bacteria comprising 27 Gram-negative and 6 Gram-positive bacteria were isolated. The antibacterial activity was demonstrated by 7 isolates in which R1L3 and TKL2 extracts exhibited significant activity against Bacillus cereus, Escherichia coli, and Proteus vulgaris. Production of IAA was exhibited by 15 isolates wherein R1S4 produced the highest IAA (20.62 μg/mL). Analysis of the 16S gene sequence revealed that RIR2, TKS2/R1L3, and R1S4/R1S5 belonged to Methylobacterium radiotolerans, Mycobacteroides abscessus, and Sphingomonas sp, respectively. The findings from this study showed that Nam-Nam plants harbored endophytic isolates with the potential to be established as a source of natural compounds that can be used to develop new anti-infection agents in the future. This is the first study to report on antibacterial activity and IAA production by endophytic bacteria from the Nam-Nam plants.